Teachers Evaluation of Concurrent and Consecutive Teacher Education Models in South-west, Nigeria - Hamdallat Taiwo Yusuf (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2022)
The provision of quality teachers is central to a nation’s education system. This study evaluated two universities, based on teacher education curriculum models (concurrent and consecutive) using Stake’s Antece-dents-Transactions-Outcomes (ATO) evaluation model, on the subject content and education components. The study was a descriptive type using a survey method. The sample comprised 514 teachers from selected secondary schools (188 consecutive and 326 concurrent), Research instrument was the Teachers Questionnai-re on Evaluation of Models of Teacher Education Curricula (TQEMTEC). The results indicated that teachers rated the consecutive teacher education curriculum model to be better. On the improvements needed, teacher educators suggested the inclusion of special education and more subject contents area for students enrolled in the concurrent, and an increase in the number of years for the pedagogical and practical aspects of the consecutive models. Results of the hypotheses indicated a significant difference between the views of tea-chers exposed to the concurrent and those exposed to consecutive teacher education models on subject con-tent, (t =2.47; df=512; Sig= 0.014< p 0.05). Based on the findings, a recommendation was made that the two models of teacher education should be further strengthened through improved subject content, particu-larly for the concurrent teacher education program.